Word catheter and marsupialisation in women with a cyst or abscess of the Bartholin gland (WoMan‐trial): a randomised clinical trial. (19th September 2016) - Kroese, JA; van der Velde, M; Morssink, LP; Zafarmand, MH; Geomini, P; van Kesteren, PJM; Radder, CM; van der Voet, LF; Roovers, JPWR; Graziosi, GCM; van Baal, WM; van Bavel, J; et al.
Abstract : Objective: To compare recurrence of a cyst or abscess of the Bartholin gland after surgical treatment using a Word catheter or marsupialisation. Design: Multicentre, open‐label, randomised controlled trial. Setting: Eighteen hospitals in the Netherlands and one hospital in England. Population: Women with a symptomatic cyst or abscess of the Bartholin gland. Methods: Women were randomised to treatment with Word catheter or marsupialisation. Main outcome measures: The primary outcome was recurrence of the cyst or abscess within 1 year of treatment. The secondary outcomes included pain during and after treatment (measured on a 10‐point scale), use of analgesics, and time from diagnosis to treatment. Analysis was by intention‐to‐treat. To assess whether marsupialisation would reduce the recurrence rate by 5% (from 20 to 15%) we needed to include 160 women (alpha error 0.05, beta error 0.2). Results: One hundred and sixty‐one women were randomly allocated to treatment by Word catheter ( n = 82) or marsupialisation ( n = 79) between August 2010 and May 2014. Baseline characteristics were comparable. Recurrence occurred in 10 women (12%) allocated to Word catheter versus eight women (10%) allocated to marsupialisation: relative risk (RR) 1.1, 95% confidence interval (CI) 0.64–1.91; P = 0.70. Pain scores after treatment were also comparable. In the first 24 hours after treatment, 33% used analgesics in the Word catheter group versus 74% in the marsupialisation group ( P < 0.001). Time from diagnosis to treatment was 1 hour for placement of Word catheter versus 4 hours for marsupialisation ( P = 0.001). Conclusions: In women with an abscess or cyst of the Bartholin gland, treatment with Word catheter and marsupialisation results in comparable recurrence rates. Tweetable abstract: Comparable recurrence rates for treatment of Bartholinic abscess/cyst with Word catheter and marsupialisation. Tweetable abstract: Comparable recurrence rates for treatment of Bartholinic abscess/cyst with Word catheter and marsupialisation.